Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1001/jamaophthalmol.2019.3103
|View full text |Cite
|
Sign up to set email alerts
|

Current Prevalence of Myopia and Association of Myopia With Environmental Factors Among Schoolchildren in Japan

Abstract: IMPORTANCE Given the estimates of increasing prevalence of myopia, especially in Asia, it is important to determine the current prevalence of myopia among populations of schoolchildren in Japan.OBJECTIVE To investigate the current prevalence rate of myopia and the association between environmental factors and myopia in Japanese schoolchildren. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional study assessed 1478 participants, including 726 elementary school students and 752 junior high school students, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
98
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(117 citation statements)
references
References 38 publications
11
98
1
Order By: Relevance
“…Our study found prevalence of myopia and high myopia was high in both elementary school students and high school students. A similarly high prevalence rate of myopia (76.5% in elementary school and 94.9% in junior high school) and high myopia (4.0% in elementary school, and 11.3% in junior high school) were recently reported in Japanese school students [16]. The high rate of myopia in both Japanese and Chinese students may be due to large amount of near work activities and limited time on outdoor activities, as students in China and Japan have high education pressure and are in the very competitive learning environment even among elementary school students.…”
Section: Discussionmentioning
confidence: 73%
“…Our study found prevalence of myopia and high myopia was high in both elementary school students and high school students. A similarly high prevalence rate of myopia (76.5% in elementary school and 94.9% in junior high school) and high myopia (4.0% in elementary school, and 11.3% in junior high school) were recently reported in Japanese school students [16]. The high rate of myopia in both Japanese and Chinese students may be due to large amount of near work activities and limited time on outdoor activities, as students in China and Japan have high education pressure and are in the very competitive learning environment even among elementary school students.…”
Section: Discussionmentioning
confidence: 73%
“…Asia. 47,48 In the future, because this tendency may intensify, it is important to improve the accuracy of refractive calculations in eyes with a high AL/CR ratio.…”
Section: Discussionmentioning
confidence: 99%
“…At the 20-year Raine Study follow-up, conducted between 2010 and 2012, the prevalence of myopia was 23.7% and of pterygium was 1.2% in a population of young Australian adults 63 65–67. However, the prevalence of myopia is increasing worldwide,93 98 99 with more than half of the Australasia population predicted to by myopic by the year 2050 93. Therefore, an update in prevalence of myopia is indicated and this will be addressed by the current study.…”
Section: Methods and Analysismentioning
confidence: 90%